La planification régionale en Haïti - Ernst A. Bernardin (Unité Mixte de Recherche 8504 Géographie-cités, 1999)
Since the Regionalization and physical planning law has been promulgated in 1982 and after the vote of the Constitution on March 29, 1987, the traditional macro-economic and sectorial planning system, without spatial dimension, has been put in question in Haïti in favor of a new approach evolving around the necessary integration of the spatial dimension in the elaboration of economic and social development Plans and Programs. Contrary to the old habits based on excessive centralization, the article 81 of the new Constitution of Haïti indicates a real willingness to promote decentralization: «The departmental Council has to elaborate the departmental development Plan with the support of the Public Administration sector». It is in this context that the actual planning problematic must be understood: it involves, without contest, the active participation of territorial and local collectivities at all levels of decisions making. However, territorial planning in Haïti is facing a lot of problems: The Constitution has established, since 1987, some mechanisms to put in place in order to promote decentralization in Haïti, but until now the new planning system based on decentralization is still in gestation. All structures that have been anticipated by Constitution, even when they exist, are not functional. Therefore, no departmental Plan has not emerged yet, in spite of the constitutional injunctions that are twelve years old. The actual study offers a diagnosis of the economic and social situation of Haïti and analyses the methodological frame and the necessary instruments for elaborating departmental Plans in Haïti. It insists on the adequate functioning of a national planning frame (National Scheme of physical planning) to be used as a guide in elaborating departmental Schemes of physical planning and departmental Plans.